Conserved perception of host and non-host signals via the a-pheromone receptor Ste3 in Colletotrichum graminicola - Rudolph, Anina Yasmin; Schunke, Carolin; Nordzieke, Daniela Elisabeth (Frontiers in Fungal Biology, 2024)
Understanding the interactions between fungal plant pathogens and host roots is crucial for developing effective disease management strategies. This study investigates the molecular mechanisms underpinning the chemotropic responses of the maize anthracnose fungus Colletotrichum graminicola to maize root exudates. Combining the generation of a deletion mutant with monitoring of disease symptom development and detailed analysis of chemotropic growth using a 3D-printed device, we identify the 7-transmembrane G-protein coupled receptor (GPCR) CgSte3 as a key player in sensing both plant-derived class III peroxidases and diterpenoids. Activation of CgSte3 initiates signaling through CgSo, a homolog to the Cell Wall Integrity Mitogen-Activated Protein Kinase (CWI MAPK) pathway scaffold protein identified in other filamentous fungi, facilitating the pathogen's growth towards plant defense molecules. The NADPH oxidase CgNox2 is crucial for peroxidase sensing but not for diterpenoid detection. These findings reveal that CgSte3 and CWI MAPK pathways are central to C. graminicola's ability to hijack plant defense signals, highlighting potential targets for controlling maize anthracnose.